2017
DOI: 10.5380/ce.v22i4.51503
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Nutricional De Pacientes Com Câncer Em Atendimento Ambulatorial

Abstract: RESUMO: Objetivou-se analisar o aspecto nutricional de pacientes oncológicos em atendimento ambulatorial, em Joaçaba-SC. Estudo transversal, que utilizou a avaliação subjetiva global produzida pelo paciente e questionário de consumo alimentar, do Ministério da Saúde. Participaram 70 pacientes, idade média 60,3±13,9 anos, 38 (54,3%) homens, 57 (81,4%) sem acompanhamento nutricional, 48 (68,6%) com alimentação regular, 16 (22,9%) alimentação adequada e seis (8,6%) boa alimentação. O fumo teve associação com cânc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
(10 reference statements)
1
3
0
9
Order By: Relevance
“…(24) Some researchers have reported that insufficient food intake, type of cancer, disease progression, and chemotherapy are responsible for the loss of fat and muscle mass. (18) This study found 24.2% of patients with body fat depletion and 51.4% with severe or moderate muscle mass depletion, in agreement with the estimated prevalence of malnutrition in cancer patients from 40 to 80%. (7) Another study detected malnutrition in 60% of patients based on arm circumference, and 73.3% using muscle circumference.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…(24) Some researchers have reported that insufficient food intake, type of cancer, disease progression, and chemotherapy are responsible for the loss of fat and muscle mass. (18) This study found 24.2% of patients with body fat depletion and 51.4% with severe or moderate muscle mass depletion, in agreement with the estimated prevalence of malnutrition in cancer patients from 40 to 80%. (7) Another study detected malnutrition in 60% of patients based on arm circumference, and 73.3% using muscle circumference.…”
Section: Discussionsupporting
confidence: 88%
“…This study had a predominance of male participants (56.6%), which is similar to a study with 70 subjects (54.3%). (18) Regarding nutritional status, male participants presented higher severity. This representativeness may be associated with their resistance to seeking health services, a behavior rooted in our society and still frequent.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of these conditions is variable and might range from 40 to 80% in individuals with head and neck cancer (HNC) [1] and occur due to local and metabolic changes of large magnitude that are produced by tumor cells, their growth and the secondary effects of antineoplastic treatments [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…O tratamento de radioterapia e/ou quimioterapia é capaz de provocar distúrbios gastrointestinais, que podem limitar a aceitação da dieta como, constipação e/ou diarreia, náuseas, vômitos, mucosites e a disgeusia que faz com que ocorra um aumento da viscosidade salivar e atrofia das papilas gustativas, o que acaba dificultando a percepção do paladar e da temperatura, criando uma barreira mecânica de saliva que dificulta o contato físico com os alimentos. Tais alterações no sabor dos alimentos, afetam negativamente a ingestão alimentar resultando em aversões alimentares (PALMIERI et al, 2013;FERREIRA et al, 2013;BARRÉRE et al, 2017;DALLACOSTA et al, 2017).…”
Section: Revisão Bibliográficaunclassified